Mainstreaming informal employment and gender in poverty reduction : a handbook for policy-makers and other stakeholders - Chen, Martha Alter (New gender mainstreaming series on development issues., 2004)
In this book, the authors highlight the lack of attention to employment, and especially informal employment, in poverty reduction strategies and point to the links between being informally employed, being a woman or a man, and being poor. They do this within the context of major changes relating to economic restructuring and liberalization and map out the impacts on different categories of informal producers and workers, both men and women. The book draws widely on recent data and evidence of the global research policy network called Women in Informal Employment: Globalizing and Organizing (WI.